REDESAIN PASAR BUHA KOTA MANADO DENGAN PENDEKATAN SUSTAINABLE ARCHITECTURE - Rumteh, cheril; Warouw, Felly Ferol; Attaufiq, Muhammad Muhdi (Program Studi Arsitektur Fakultas Teknik Universitas Negeri Manado, 2024)
The market is a place for sellers and buyers. This is due to the transaction process of goods/services and the bargaining that occurs. The characteristics of the market usually consist of stalls / stalls, and open lots available to traders. The appearance or overall feel of a shopping center that can make the market stand out among its competitors such as the facilities and infrastructure provided. In general, it is an area used for selling places that traders use as a means or facility in placing goods from services for sale. This is due to Pasar Buha which is a